Analysis of Intellectual Capital Research Trends: A Comprehensive Review of the Last Decade's Academic Literature - Rachmawati, Rima; Abdul Halim, Radhi; Arifian, Andry; Cosa, Kenneth; Abu, Janine (Politeknik Ganesha Medan, 2024)
This study examines the evolution of Intellectual Capital (IC) literature from 1997 to 2023 using Scopus. It employs a systematic literature review, integrating bibliometrics to analyze 790 studies. Findings reveal a marked increase in IC publications since 2004, identifying five IC sub-dimensions: human, structural, organizational, process, and relational/social customer capital. The study emphasizes IC’s role in innovation and value creation. It concludes that IC is crucial in modern business, linking it to company performance and wealth creation. Future research should explore IC's specific aspects and impact on organizational digital transformation.